Bilingual education as an instrument of ethnic minority protection - Zorman, Anja (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2021)
The educational system is an essential form of institutional support to ethnolinguistic vitality. In the bilingual areas of the Slovene Littoral, Italian as minority language is offered in schools with Slovene as language of instruction as a compulsory subject with the aim of educating learners for interethnic and intercultural communication. The article discusses the relationships between social and individual factors in the development of communicative competence in the minority language. Data were collected by means of a Likert scale questionnaire. The results reveal the language behaviour of Slovene speakers as age related and strongly associated to the subjective relevance of Italian in their private life. Differences in contact with Italian were also observed, however they appear to be more related to levels of language proficiency than age.
Keywords: bilingual education; dvojezično izobraževanje; ethnolinguistics; etnolingvistika; Italian minority; Italianlanguage; italijanska manjšina; italijanščina; Slovene Littoral; Slovenia; Slovenija; Slovensko primorje